Atypical presentation of the Wellens electrocardiographic pattern associated with coronary bifurcation lesion - Alca-Clares, Raul (2021)
We present a patient who was admitted to the emergency room due to unstable angina, with an initial electrocardiogram without signs of acute ischemia and a favorable clinical evolution. During hospitalization, she developed the Wellens electrocardiographic pattern, noted in the literature as an infrequent, poorly identified finding and with an ominous prognosis. This electrocardiographic pattern is described in precordial derivatives, suggesting a significant lesion of a principal epicardial artery; our patient had similar electrocardiographic alterations in the high lateral leads, in whom the coronary bifurcation lesion not previously described in this scenario was confirmed.